Prevention of Parenteral Nutrition-associated Cholestasis Using Reduced Dose Soybean Lipid Emulsion: A Multicenter Randomized Trial - Maselli, Kathryn M.; Carter, Irene C.; Matusko, Niki; Warschausky, Seth; Blackmer, Allison B.; Islam, Saleem; Rollins, Michael D.; Javid, Patrick J.; Arnold, Meghan A. (Journal of pediatric surgery, 2024)
Reducing soybean lipid emulsion (SLE) dose may prevent parenteral nutrition-associated cholestasis (PNAC) but effects on growth and neurodevelopment are unknown. The purpose of this study was to evaluate the effect of reduced dose SLE on growth and neurodevelopment. Surgical neonates at 4 centers were randomized to standard SLE (3 g/kg/day) or reduced SLE (1 g/kg/day) over a 12-week period. Bilirubin levels and growth parameters were measured baseline and weekly while on study. The effects of time and group on direct bilirubin and growth were evaluated with a linear mixed effects model. Neurodevelopmental outcomes were assessed at 12- and 24-months corrected gestational age. Twenty-one individuals were randomized (standard dose = 9, reduced dose = 12). Subjects in the reduced dose group had slower rates of direct bilirubin increase and overall levels decreased earlier than those in the standard dose group. There was a trend toward a faster direct bilirubin decrease in the reduced dose group (p = 0.07 at day 84). There were no differences in the rates of change in weight (p = 0.352 at day 84) or height Z-scores (p = 0.11 at day 84) between groups. One subject in the reduced dose group had abnormal neurodevelopmental testing at 24 months. Surgical neonates randomized to a reduced dose of SLE had improved trends in direct bilirubin levels without clinically significant differences in overall growth and neurodevelopment. Randomized Controlled Trial. II. •Reduced soybean lipid emulsion dose may prevent the development of PNAC in surgical neonates but the effects on long term growth and neurodevelopment are not known•Here we demonstrate that surgical neonates receiving reduced dose soybean lipid emulsion had improved bilirubin trends without significant differences in growth or neurodevelopment